Peningkatan Vitalitas Kawasan Bersejarah Melalui Strategi Retrofitting di Kota Lama Padang - Dwi Luthfiya Yumna; Muhammad Sani Roychansyah (Jurnal Talenta Sipil, 2026)
The Padang Old Town area is a historic urban district that has experienced a decline in vitality due to physical deterioration, shifts in the city’s economic center, and weak integration between social functions and spatial connectivity. Previous development efforts have largely been fragmented and have not succeeded in restoring the area’s dynamic urban life in a sustainable manner. These conditions indicate the need for a more adaptive and context-sensitive transformation approach that responds to both historical values and contemporary urban activities. This study aims to formulate strategies for enhancing the vitality of the Padang Old Town through an urban retrofitting approach that integrates physical improvement, social activation, and spatial connectivity. The research employs a mixed-methods approach, combining quantitative analysis through vitality mapping and identification of dominant local influencing factors with qualitative interpretation to develop area typologies and targeted intervention strategies.The findings reveal nine specific typologies derived from the synthesis of vitality quadrants and dominant spatial factors, which are subsequently consolidated into three main intervention concepts: Re-Connect, Re-Use, and Re-Activation. These concepts function to improve inter-zone accessibility, optimize existing physical assets through adaptive reuse and heritage conservation, and reactivate social and cultural dynamics by providing inclusive public spaces. This study recommends the phased implementation of retrofitting strategies based on typological priorities, supported by adaptive regulatory frameworks, to ensure sustainable urban vitality while preserving the historical identity of the Padang Old Town area.